P87 Socioeconomic inequalities in asthma, wheeze and undiagnosed wheeze across nine European cohorts. (13th September 2016) - Bird, P; Uphoff, E
Abstract : Background: In high-income countries, symptoms and diagnoses of asthma have been found to be more prevalent among people with lower socioeconomic status (SES). It is not known how these inequalities vary between countries. One complication is that different measures of SES and asthma diagnosis are used, which means that results may not be comparable between samples and countries. In addition, cross-country analyses often use wheeze as an indicator of asthma, meaning differences in undiagnosed wheeze might go unnoticed. This study explores differences in the social patterning of childhood wheeze and asthma, and the proportion of children with wheeze diagnosed with asthma, by maternal education using data from European cohort studies in the MeDALL partnership. Methods: Nine cohorts provided data on asthma, wheeze, maternal education and a range of covariates at different child ages (6 months to 16 years old): ROBBIC Italy (N = 1, 128), PARIS France (N = 1, 549), INMA Spain (N = 2, 515), BAMSE Sweden (N = 4089), PIAMA The Netherlands (N = 3, 963), LISA Germany (N = 3, 094), GINI Germany (N = 5, 991), RHEA Greece (N = 1, 336), and BiB England (N = 1, 684). Data were analysed with multilevel logistic regression models (time variable 'child age'). Results: Prevalence rates of diagnosed asthma at age 4 increased with child age and varied substantially between cohorts; from 1.72% in LISA to 13.48% in BiB. Prevalence rates of wheeze at age 4 varied from 9.82% in RHEA to 55.37% in INMA. Doctor diagnosis of asthma was associated with lower-level maternal education for the full sample. Looking at individual cohort data, prevalence rates of asthma were associated with lower-level maternal education in BAMSE (highest level OR 0.43, 95% CI 0.31; 0.59), PIAMA (highest level OR 0.50, 95% CI 0.34; 0.73), and GINI (highest level OR 0.28, 95% CI 0.15; 0.53), while no statistically significant associations were found for other cohorts. Of all children with wheeze, 28.79% were diagnosed with asthma during the study. Children with wheeze were more likely to be diagnosed with asthma if their mother had the lowest level (35.10%, 95% CI 0.33; 0.37) compared to the highest level of education (27.24%, 95% CI 0.26; 0.29) (analyses on going), 95% CI 0.26; 0.29) (analyses on-going). Conclusion: This study confirms social gradients in asthma and wheeze, but also reveals large differences in the prevalence of wheeze, asthma and wheeze without asthma diagnosis by cohort and maternal education. These findings provide insight into social inequalities in the diagnosis of asthma in Europe.